2021
DOI: 10.1002/fsn3.2266
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and antimicrobial resistance of Salmonella isolated from retail meats in Anhui, China

Abstract: Salmonella is the most common and representative pathogen isolated from confirmed cases of global foodborne diseases, which poses serious risks to human health (Cunha-Neto et al., 2017). In most cases, the transmission to humans is associated with the consumption of contaminated foods or water, the treatment of contaminated raw meat, cross-contamination, and the consumption of uncooked

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
1
13
0
Order By: Relevance
“…Owing to the excessive use of antimicrobial agents in animal husbandry over the last few decades and the horizontal spread of resistance genes, AMR in Salmonella has become a major concern ( Foley et al, 2008 ). All isolates identified in this study were MDR and were broadly resistant to conventional antimicrobials, suggesting that most bacteria have acquired resistance traits under prolonged selection pressures, which is consistent with many previous findings ( Yang et al, 2020 ; Sun et al, 2021 ; Wang et al, 2021 ). We also found variations in the resistance patterns of isolates from different periods, with the isolates obtained in the first collection period exhibiting a marked increase in resistance to EFT and newer-generation antimicrobials as well as an increase in susceptibility to TET.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Owing to the excessive use of antimicrobial agents in animal husbandry over the last few decades and the horizontal spread of resistance genes, AMR in Salmonella has become a major concern ( Foley et al, 2008 ). All isolates identified in this study were MDR and were broadly resistant to conventional antimicrobials, suggesting that most bacteria have acquired resistance traits under prolonged selection pressures, which is consistent with many previous findings ( Yang et al, 2020 ; Sun et al, 2021 ; Wang et al, 2021 ). We also found variations in the resistance patterns of isolates from different periods, with the isolates obtained in the first collection period exhibiting a marked increase in resistance to EFT and newer-generation antimicrobials as well as an increase in susceptibility to TET.…”
Section: Discussionsupporting
confidence: 91%
“…Frontiers in Microbiology 08 frontiersin.org (Yang et al, 2020;Sun et al, 2021;Wang et al, 2021). We also found variations in the resistance patterns of isolates from different periods, with the isolates obtained in the first collection period exhibiting a marked increase in resistance to EFT and newer-generation antimicrobials as well as an increase in susceptibility to TET.…”
Section: Discussionmentioning
confidence: 60%
“…Out of 26 papers selected, 15 papers were from China [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] and the rest (11 papers) were from the USA [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. The data extracted contain 13,018 food samples, out of which 5000 samples were AMR positive (2276 and 2724 from China and the USA, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to the current study, in a previous report by Hai et al [ 30 ] from China, more than 90.0% of the Salmonella isolates harbored stn and sopB genes. Also, Wang et al [ 31 ] from China reported higher incidence rates for sopB (100.0%) and spvC (93.8%) genes among Salmonella serovars isolated from 120 retail meat samples, including chicken ( n = 45), duck ( n = 30), and pork ( n = 45). In the prior studies from Iran [ 6 ], Tunisia [ 23 ], and Nigeria [ 27 ], the prevalence rates of spvC gene were 50.8%, 45.8%, and 59.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%